Vulvovaginal candidiasis: knowledge, practices and occurrence among pregnant women receiving antenatal care in a teaching hospital, Ghana - Florence Shine Edziah; Florence Shine Edziah; Princess Ruhama Acheampong; Philip Apraku Tawiah; Cedric Dzidzor Amengor; Godsway Edem Kpene; Grace Otobea Amponsah; Priscilla Appiah Baffoe; Georgina Korankye; John Gameli Deku (Frontiers in Global Women's Health)
BackgroundVulvovaginal Candidiasis (VVC) is a condition commonly caused by Candida albicans. It is the second most common infection of the female genitalia affecting many women worldwide. Studies have identified unhealthy genital care practices to be associated with the infection among women including expectant mothers. Knowledge of the various signs and symptoms is crucial for early detection, reporting, and treatment. Good knowledge may influence healthy practices, limiting the infection and its complications. This study assessed the knowledge, practices and occurrence of Vulvovaginal candidiasis among pregnant women accessing antenatal care at a teaching hospital in Ghana.MethodsA cross-sectional study was conducted among 336 pregnant women receiving antenatal care at the Ho Teaching Hospital. A structured questionnaire was used to assess their knowledge of the infection and practices on vaginal hygiene. The hospital records of these participants were further checked to verify the occurrence of the infection. Data were analyzed using Stata version 16. Analysis to identify associations between outcome variables and risk factors as well as significance level was carried out.ResultsOut of the 336 gestational mothers involved in the study, 27.1% were found to have been diagnosed with candidiasis at the time of the study. Pregnant women who usually use antibiotics had 2.25 increased odds of developing VVC compared to those who do not [OR:2.25 95CI:1.33–3.79; p-value = 0.003]. Although, good knowledge was recorded among a greater percentage of the study participants on the various signs and symptoms including vaginal discharge and its abnormalities, there was however, a poor knowledge on the causative organism, as 77.4% indicated that the infection was caused by other agents rather than fungi.ConclusionThe occurrence of VVC was elevated in the study jurisdiction. Frequent antibiotic use was found to be significantly associated with the occurrence of the infection.